2019
DOI: 10.3389/fphys.2019.01463
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Electrical Stimulation: A New Therapeutic Option for Chronic Diseases Based on Contraction-Induced Myokine Secretion

Abstract: Myokines are peptides known to modulate brain neuroplasticity, adipocyte metabolism, bone mineralization, endothelium repair and cell growth arrest in colon and breast cancer, among other processes. Repeated skeletal muscle contraction induces the production and secretion of myokines, which have a wide range of functions in different tissues and organs. This new role of skeletal muscle as a secretory organ means skeletal muscle contraction could be a key player in the prevention and/or management of chronic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 82 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…It is possible that our favorable results may be related to the characteristics of the current used that could evoke type 4 and 5 contractions. It is a fact that, even when NMES is applied for shorter periods, as in the present study, the anti-inflammatory and local circulatory effects can be perpetuated for hours [ 22 , 23 , 29 31 ]. Future studies should establish the optimal dosage of NMES.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is possible that our favorable results may be related to the characteristics of the current used that could evoke type 4 and 5 contractions. It is a fact that, even when NMES is applied for shorter periods, as in the present study, the anti-inflammatory and local circulatory effects can be perpetuated for hours [ 22 , 23 , 29 31 ]. Future studies should establish the optimal dosage of NMES.…”
Section: Discussionmentioning
confidence: 91%
“…This reduction appears to be basically associated with three mechanisms, (i) decrease in tissue pressure caused by the change in contact produced by evoked contractions [ 19 , 20 ]; (ii) local increase in microcirculation [ 32 , 33 ]; and (iii) muscle hypertrophy [ 18 ]. Furthermore, similarly to resistance exercise, NMES can promote anti-inflammatory and angiogenic effects, which may reduce the incidence of PI [ 29 31 ]. Since we did not demonstrate an increase in the muscle thickness of the gluteus maximus, we attributed the lower incidence of PI in the NMES group to a reduction in pressure areas and to an increase in tissue oxygenation in the adjacent areas.…”
Section: Discussionmentioning
confidence: 99%
“…While many of these failed to reach statistical significance or have a significant effect upon soleus CSA, this cross-over is suggestive of a systemic effect with ES not observed during ML [11]. In emulating exercise, ES promotes the secretory function of skeletal muscle, releasing circulatory factors know as ‘myokines.’ Myokines promote a cascade of endocrine, paracrine, and autocrine effects which modulate inter-organ functions [39]. Thus, myokines exert beneficial effects on a plethora of conditions not limited to muscle growth and insulin sensitizing.…”
Section: Discussionmentioning
confidence: 99%
“…Myokines promote a cascade of endocrine, paracrine, and autocrine effects which modulate inter-organ functions (42). Thus, myokines exert beneficial effects on a plethora of conditions not limited to muscle growth and insulin sensitizing.…”
Section: Potential Systemic Effectmentioning
confidence: 99%
“…For a few years, chronic ISMC has been envisaged as a potential substitute for aerobic physical exercise (EX), i.e., endurance exercise such as walking, running, cycling to improve brain health including mental health. To support this, chronic ISMC was reported to increase the production of myokines involved in neuroplasticity ( Sanchis-Gomar et al, 2019 ) as well as cerebral levels of brain-derived neurotrophic factor (BDNF) ( Ke et al, 2011 ; Dalise et al, 2017 ) a neurotrophin playing a crucial role in EX-induced synaptic plasticity, neurogenesis and cognition ( Vaynman et al, 2004 ; Lu et al, 2008 ; Erickson et al, 2012 ). There are also studies that reported an improvement by chronic ISMC of the negative psychological state associated with spinal cord injury ( Twist et al, 1992 ) and memory impairment in Alzheimer’s patients ( Scherder et al, 1995 ).…”
Section: Introductionmentioning
confidence: 99%